Respuesta :

26.

Given

  • A = 2πr² +2πrh

Find

  • h

Solution

There are a couple of ways to do this, depending on the form of the result you want. You can divide by the coefficient of h, then add the opposite of the constant on the side of the equation with h. Or, you can do these steps in reverse order.

... A/(2πr) = r + h . . . . divide by h coefficient

... h = A/(2πr) - r . . . . first approach

___

... (A - 2πr²) = 2πrh . . . . . . subtract the non-h term

... h = (A - 2πr²)/(2πr) . . . . second approach